Нафтогазоносність Приазовської частини південного схилу Українського щита: напрями пошуків, перспективи приросту запасів та відкриття нових родовищ - Верховцев, В.Г.; Євдощук, М.І.; Клочко, В.П.; Максимчук, П.Я.; Чебаненко, І.І.; Задорожна, Н.В. (Видавничий дім "Академперіодика" НАН України, 2007)
The geological structure, petroleum potential, and searching prospects of hydrocarbons in the margin of the near-Azov part of the southern slope of the Ukrainian shield are analyzed. By the results of neotectonic studies, the neotectonic structural position of the Priazovskoe gas field is determined, and new prospective areas within the surrounding territory are proposed.